2020
DOI: 10.35732/ctlabp.2020.6.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm Effect of Bioconversion of Whey by Lactic Acid Bacteria against Foodborne Pathogenic Bacteria

Abstract: Whey is a major by-product of cheese manufacture and contains many valuable constituents, such as β-lactoglobulin, lactoferrin and immunoglobulin. The current study determined the anti-biofilm activity of bioconversion of whey by Lactobacillus plantarum (LP-W), L. rhamnosus GG (LR-W), L. brevis (LB-W) and Enterococcus faecium (EF-W) against foodborne pathogenic bacteria, Escherichia coli O157:H7 and Listeria monocytogenes. When the foodborne pathogenic bacteria were co-incubated with LP-W, LR-W, LB-W or EF-W, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The mechanism of antimicrobial activity by PMB has also been suggested. PMB using whey showed antimicrobial activity that reduced Escherichia coli and Listeria monocytogenes ( Lee et al, 2020 ). This result suggested that quorum sensing and intercellular connections to form a biofilm structure composed of a bacterial community and extracellular polymeric matrix were inhibited by PMB with whey.…”
Section: Probiotics-mediated Bioconversion (Pmb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of antimicrobial activity by PMB has also been suggested. PMB using whey showed antimicrobial activity that reduced Escherichia coli and Listeria monocytogenes ( Lee et al, 2020 ). This result suggested that quorum sensing and intercellular connections to form a biofilm structure composed of a bacterial community and extracellular polymeric matrix were inhibited by PMB with whey.…”
Section: Probiotics-mediated Bioconversion (Pmb)mentioning
confidence: 99%
“…In addition, a comparative analysis of the inhibitory effects of KetoC and KetoB against P. gingivalis showed that only KetoC lowered the viability and proliferation rate of P. gingivalis ( Sulijaya et al, 2019 ). According to Lee et al (2020) study, PMB of whey showed anti-biofilm effect against pathogenic bacteria. The PMB of olive produces oleuropein, a type of phenolic compound, which exhibits antimicrobial activity ( Omar, 2010 ).…”
Section: Probiotics-mediated Bioconversion (Pmb) and Periodontitismentioning
confidence: 99%